2010
DOI: 10.2147/jmdh.s14900
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation to more health promotion in health services – a study of barriers and possibilities from the perspective of health professionals

Abstract: Aim:The objective of this study is to analyze the commitment to a more health-promoting health service and to illuminate important barriers for having a health-promoting role in daily practice, among Swedish health care professionals.Material and method:Out of a total of 3751 health professionals who are working daytime in clinical practice in the province of Västerbotten, 1810 were invited to participate in a survey. The health professionals represented eight different occupational groups: counselors, dietici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 32 publications
(41 reference statements)
10
85
0
1
Order By: Relevance
“…These particularities of the participants to Health-Expo campaigns were observed at other similar events organized in several cities of Romania [13,27]. These disproportionalities are very likely a result of self-selection and might be attributed to a heightened interest of women and the elderly toward their health status [28][29][30]. Supposedly, other factors specific to the elderly, such as the availability of free time and a stronger need for socialization might explain their overrepresentation in the studied sample.…”
Section: Discussionsupporting
confidence: 58%
“…These particularities of the participants to Health-Expo campaigns were observed at other similar events organized in several cities of Romania [13,27]. These disproportionalities are very likely a result of self-selection and might be attributed to a heightened interest of women and the elderly toward their health status [28][29][30]. Supposedly, other factors specific to the elderly, such as the availability of free time and a stronger need for socialization might explain their overrepresentation in the studied sample.…”
Section: Discussionsupporting
confidence: 58%
“…This fact may partially explain why Swedish doctors initiate fewer discussions about lifestyle. A Swedish survey showed that among primary care personnel, 69% stated that health services should make prevention the priority rather than treatments, and 60% reported willingness to do more health promotion and disease prevention [27]. However, the same study also revealed that 87% of the primary care personnel experienced heavy workload/lack of time as a core constraint for health promotion and disease prevention in practice.…”
Section: Discussionmentioning
confidence: 99%
“…They complained that the public, their collaborators from other fields and public officials are all unaware of their competencies in health promotion. Johansson et al (23) have observed that some professions, among them occupational therapists, are not usually associated with health promotion, even though they have the knowledge and desire to focus on it more intensively. The same authors state that officials have a responsibility to utilize the knowledge of these professionals and facilitate their participation in health promotion work (23).…”
Section: Discussionmentioning
confidence: 99%
“…Johansson et al (23,24) identified heavy workloads, lack of guidelines and unclear objectives as significant obstacles for OTs and other health professionals to broaden the role of health promotion in the health service. The authors also found that the understanding of holism in health seems to be there.…”
Section: Introductionmentioning
confidence: 99%